ANALISIS KONTEN TRIPLE DIALOGUE PADA AKUN INSTAGRAM @KATOLIK_GARIS_LUCU - Deimen Wahana Utama, Atanasius; Rosario Babtista, Thomas; Borromeus Mulyatno, Carolus (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Social media is a means for people to connect with each other quickly across borders. Today, social media has become an important necessity, one of which is to communicate. The need to communicate on social media is facilitated by various digital platforms, especially Instagram. In this study, researchers will focus on the Instagram account @katolik_garis_lucu. The @katolik_garis_lucu Instagram account is one of the accounts that is in demand not only by Catholic users, but from diverse users. With the distinctive style of @katolik_garis_lucucu Instagram account uploads, namely humor, the account provides a color about the plurality that exists in Indonesia. The purpose of this study is to analyze the content in the @katolik_garis_lucu Instagram account using the Asian Triple Dialogue theory. This study limits content analysis to the @katolik_garis_lucu Instagram account for the period April 23-September 20, 2023. In this study, the Asian Triple Dialogue includes three things, namely religion, culture, and poverty.Â